Localized Detection of Abandoned Luggage. (29th June 2010) - Chang Chang, Jing-Ying Jing-Ying; Liao Liao, Huei-Hung Huei-Hung; Chen Chen, Liang-Gee Liang-Gee
Abstract : Abandoned luggage represents a potential threat to public safety. Identifying objects as luggage, identifying the owners of such objects, and identifying whether owners have left luggage behind are the three main problems requiring solution. This paper proposes two techniques which are "foreground-mask sampling" to detect luggage with arbitrary appearance and "selective tracking" to locate and to track owners based solely on looking only at the neighborhood of the luggage. Experimental results demonstrate that once an owner abandons luggage and leaves the scene, the alarm fires within few seconds. The average processing speed of the approach is 17.37 frames per second, which is sufficient for real world applications.